War feels less horrid in a foreign accent: exploring the impact of the foreign accent on emotionality - Bazzi, Luca; Brouwer, Susanne; Khan, Zoha Nisar; Verdonschot, Rinus G.; Foucart, Alice (Frontiers in Language Sciences, 2024)
The processing of a foreign accent is known to increase cognitive load for the native listener, establish psychological distance with the foreign-accented speaker, and even influence decision-making. Similarly, research in the field of emotional processing indicates that a foreign accent may impact the native listener's emotionality. Taking these aspects into consideration, the current study aimed to confirm the hypothesis that a foreign accent, compared to a native accent, significantly affects the processing of affective-laden words. In order to test this hypothesis, native Spanish speakers participated in an online experiment in which they rated on a Likert scale the valence and arousal of positive, neutral and negative words presented in native and foreign accents.Results confirm a foreign accent effect on emotional processing whereby positively valenced words are perceived as less positive and negatively valenced words as less negative when processed in a foreign accent compared to a native accent. Moreover, the arousal provoked by emotion words is lesser when words are processed in a foreign than a native accent. We propose possible, not mutually exclusive, explanations for the effect based on linguistic fluency, language attitudes and the linguistic context of language acquisition. Although further research is needed to confirm them, these explanations may be relevant for models of language comprehension and language learning. The observation of a reduction in emotionality resulting from a foreign accent is important for society as important decisions are made by representatives with diverse language and accent backgrounds. Our findings demonstrate that the choice of the language, which entails speaking in a native or a foreign accent, can be crucial when discussing topics such as the consequences of wars, pandemics, or natural disasters on human beings.